Acidimangrovimonas sediminis gen. nov., sp. nov., isolated from mangrove sediment and reclassification of Defluviimonas indica as Acidimangrovimonas indica comb. nov. and Defluviimonas pyrenivorans as Acidimangrovimonas pyrenivorans comb. nov. Issue 8 (6th June 2019) - Ren, Hao; Ma, Hui; Li, Hao; Huang, Lingfeng; Luo, Yuanrong
Abstract : A Gram-stain-negative, aerobic, non-motile, short-rod bacterium, strain MS2-2 T, was isolated from mangrove sediment sampled at Jiulong River Estuary, Fujian province, PR China. 16S rRNA gene sequence similarity analysis showed that strain MS2-2 T was most closely related to Defluviimonas indica 20V17 T (97.41 %) and Defluviimonas pyrenivorans PrR001 T (96.18 %). Phylogenetic trees based on 16S rRNA genes and genome sequences both revealed that strain MS2-2 T formed a distinct cluster with D. indica 20V17 T and D. pyrenivorans PrR001 T within family Rhodobacteracea, quite separate from other type species in the genus Defluviimonas . The average nucleotide identity value between strain MS2-2 T and D. indica 20V17 T was 78.35 %. Growth of strain MS2-2 T was observed at 16–41 ° C (optimum, 34 ° C), pH 3.6–7.5 (pH 6.0) and 0.5–10.0 % (w/v) NaCl (4.0 %). The major cellular fatty acids were summed feature 8 (C18 : 1 ω7 c and/or C18 : 1 ω6 c ), C16 : 0 and C18 : 0 . Ubiquinone 10 was the sole quinone. The major polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. The DNA G+C content was 67.9 mol%. The combined genotypic and phenotypic data show that strain MS2-2 T represents a novel species of a novel genus in the family Rhodobacteraceae, for which the name Acidimangrovimonassediminis gen. nov., sp. nov. is proposed, with the type strain MS2-2 T (=MCCC 1K02682 T =NBRC 112978 T ). We also propose the reclassification of Defluviimonas indica as Acidimangrovimonas indica comb. nov. and Defluviimonas pyrenivorans as Acidimangrovimonas pyrenivorans comb. nov.